Eating disorders in older women. Issue 2 (October 2015) - Podfigurna-Stopa, Agnieszka; Czyzyk, Adam; Katulski, Krzysztof; Smolarczyk, Roman; Grymowicz, Monika; Maciejewska-Jeske, Marzena; Meczekalski, Blazej
Highlights Eating disorders (EDs) are psychiatric disturbances that seriously endanger the physical health and often the lives of affected patients and disorganise their psychosocial functioning. The incidence of EDs in older women has increased in recent decades. The weight loss and malnutrition resulting from EDs have widespread negative consequences for physical, mental and social health. EDs are serious illnesses and they should never be neglected or treated only as a manifestation of the fashion for dieting or a woman's wish to achieve an imposed standard feminine figure.